Sistem Pendukung Keputusan Penentuan Pegawai Terbaik Menggunakan Metode Fuzzy AHP - Yudara, I Gede; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
In determining the best employees in the company can spur employee enthusiasm in working, because the company will provide incentives or bonuses for these employees. However, in determining the best employee, several parameters and criteria are needed so that the assessment is carried out on target. The improved performance of employees will certainly have a direct impact on the quality of company services. Employee performance appraisal is carried out by a human resort management (HRD) director and the assessment consists of a number of criteria. The assessment will be difficult if done manually considering that each assessor has their own preferences in conducting the assessment. To overcome this we need a computer system that helps decision making in determining the best employees, namely a decision support system (SPK) for determining the best employees in the company. The decision support system developed in this study uses the Fuzzy Analitycal Hirarcy Process (AHP) method to assist decision making. Fuzzy AHP method is used for decision making in each assessor. Based on the final results of the best employee determination system in the form of ranking the final value of each employee. The highest value is used as a recommendation as the best employee in the company.